Pengaruh Integrative Leadership Terhadap Organizational Citizenship Behavior (OCB) Karyawan pada PT Pelindo Cabang Teluk Bayur Padang dengan Employee Engagement sebagai Variabel Moderasi - Larasati Deparas; Sulastri Sulastri (Jurnal Kajian Manajemen dan Wirausaha, 2019)
Purpose- This research analyzed: (1) The influence of integrative leadership on employee engagement at PT PELINDO (2) The influence of employee engagement on organizational citizenship behavior at PT PELINDO (3) The influence of integrative leadership on organizational citizenship behavior at PT PELINDO (4) The influence of integrative leadership on organizational citizenship behavior through employee engagement at PT PELINDO.Methodology - This research is descriptive causative research. The population were all employee in the PT PELINDO, amounting to 72 people. The number of samples was determined using total sampling technique. This research analyzed using path analysis with SmartPLS3.Finding - Regarding the partial mediation model proposed, the data confirm the relationship set out in the hypothesis. This research found that (1) integrative leadership has  positive and significant effect employee engagement in PT PELINDO (2) employee engagement has a positive and significant effect on organizational citizenship behavior in PT PELINDO (3) integrative leadership has a positive and significant effect on organizational citizenship behavior in PT PELINDO (4) Employee engagement mediates the relationship between integrative leadership and organizational citizenship behavior. Keywords: Organizational Citizenship Behavior, Integrative Leadership, Employee Engagement